Valorization of residual biomass from the hydrocolloid industry: The role of hydrothermal treatments in the recovery of high-value compounds - Gomes-Dias, Joana S. (2024)
Gelidium seaweeds are recognized for their high-quality hydrocolloids, but their industrial extraction leaves behind biomass, whose available valorization approaches are not economically and/or environmentally sustainable. This work aimed to evaluate, for the first time, the effect of batch hydrothermal treatments (and their severity (S0)) on the fractionation of carbohydrates and proteins from this residue. At S0  3.13, agars with a maximum gelling strength of 185 g/cm2 can be obtained. At S0 = 3.46, galactose-based non-gelling oligosaccharides are recovered. Harsher processing conditions (S0  2.23) result in higher protein solubilization and antioxidant activity. Moreover, sequential processing is a feasible approach to improve process selectivity. A novel proposed two-step hydrothermal treatment (at 200 °C and 230 °C), results in maximum oligosaccharide and protein recovery, leaving behind a cellulose-enriched solid that can be used for biofuel production, in a biorefinery approach.